Taking matters into our own hands: influencing factors and concerning factors for libraries that developed Open Source Software - Greenhill, Kathryn (VALA: Libraries, Technology and the Future, 2010)
Libraries that develop Open Source library software are influenced by a number offactors. The insights from this group are useful for library staff who are consideringadopting Open Source library software. The author surveyed and interviewed staffwho developed Scriblio, SOPAC2, VUFind, Blacklight, Koha and Evergreen. Shealso interviewed librarians who specified the Open Library Environment. Theinterviews and questionnaires revealed a common attitude to the cost of OpenSource Software; similar concerns about speed and process for enhancements toproprietary library software; and similar satisfaction with the control and communitythat Open Source software has brought to their library operations.